High surface-area carbon microcantilevers. Issue 3 (3rd January 2019) - Noyce, Steven G.; Vanfleet, Richard R.; Craighead, Harold G.; Davis, Robert C.
Abstract : Fully-porous carbon resonators were formed with precise microscale dimension and characterized for sensitive detection of vapors. Abstract : Microscale porous carbon mechanical resonators were formed using carbon nanotube templated microfabrication. These cantilever resonators exhibited nanoscale porosity resulting in a high surface area to volume ratio which could enable sensitive analyte detection in air. These resonators were shown to be mechanically robust and the porosity could be controllably varied resulting in densities from 10 2 to 10 3 kg m −3, with pore diameters on the order of hundreds of nanometers. Cantilevers with lengths ranging from 500 μm to 5 mm were clamped in a fixture for mechanical resonance testing where quality factors from 10 2 to 10 3 were observed at atmospheric pressure in air.